Makna idiomatis arab-indonesia pada konten youtube mrbeast: 1000 orang buta melihat untuk pertama kali - luthfiyyah, nurul (Maliki Interdisciplinary Journal, 2025)
This article contains problems with words containing idiomatic meanings in MrBeast's YouTube content. Many YouTube users have watched this content, around 181 million viewers. The author finally made MrBeast content the object of research using qualitative descriptive methods. This research aims to reveal the idiomatic meaning contained in the video content produced by Mr. Beast, a famous YouTuber. Qualitative descriptive methods are used to describe various idioms and expressions used in Mr. Beasts. Data was collected from his videos entitled '1000 People Watching for the First Time'. The results of the analysis show that speakers in this content use idioms and expressions that not only have literal meanings, but also contain distinctive figurative or idiomatic meanings. This idiomatic use can influence how viewers understand and interpret the video content. This study provides a deeper understanding of how content uses language to effectively communicate complex messages to its audience via digital platforms.